A Probabilistic Model for Indel Evolution: Differentiating Insertions from Deletions. (1st September 2021) - Loewenthal, Gil; Rapoport, Dana; Avram, Oren; Moshe, Asher; Wygoda, Elya; Itzkovitch, Alon; Israeli, Omer; Azouri, Dana; Cartwright, Reed A; Mayrose, Itay; Pupko, Tal
Abstract: Insertions and deletions (indels) are common molecular evolutionary events. However, probabilistic models for indel evolution are under-developed due to their computational complexity. Here, we introduce several improvements to indel modeling: 1) While previous models for indel evolution assumed that the rates and length distributions of insertions and deletions are equal, here we propose a richer model that explicitly distinguishes between the two; 2) we introduce numerous summary statistics that allow approximate Bayesian computation-based parameter estimation; 3) we develop a method to correct for biases introduced by alignment programs, when inferring indel parameters from empirical data sets; and 4) using a model-selection scheme, we test whether the richer model better fits biological data compared with the simpler model. Our analyses suggest that both our inference scheme and the model-selection procedure achieve high accuracy on simulated data. We further demonstrate that our proposed richer model better fits a large number of empirical data sets and that, for the majority of these data sets, the deletion rate is higher than the insertion rate.